Education Institution Internet Of Things (IOT) Online Dashboard For Academic Data Sharing - Syafiq Fauzi, Kamarulzaman (Centre for Applied Learning and Multimedia, UNIMAS, 2019)
Various Internet of Things (IoT) devices are currently being developed by academician and students wise for various type of research. However, platform for sharing the results and data in form of visualisations and raw data is limited, while some involve commercial elements which restricts the freedom as academician. This project proposes an Education Institution IoT Online Dashboard for academic data sharing. Academician and students have the freedom to share the results of their research using the dashboard, thus increasing public exposure for their academic projects.